A Au@Pt bimetallic nanoparticle and blue silica nanoparticle nanocomposite as a probe of immunochromatographic assay for HBsAg detection. Issue 48 (25th November 2019) - Liu, Jing; Yu, Qiongqiong; Zhao, Guangying; Dou, Wenchao
Abstract : In this article, a sensitive, visual and quantitative immunochromatographic assay (ICA) is described by using a novel Au@Pt-nanoparticle-decorated blue-silica-nanoparticle nanocomposite (Au@Pt/blue SiNPs) as a reporter probe. Abstract : In this article, a sensitive, visual and quantitative immunochromatographic assay (ICA) is described by using a novel Au@Pt-nanoparticle-decorated blue-silica-nanoparticle nanocomposite (Au@Pt/blue SiNPs) as a reporter probe. The Au@Pt/blue SiNPs were prepared by using post-modification methods, in which Au@Pt NPs were synthesized on the surface of blue SiNPs. The antibody against HBsAg was conjugated with Au@Pt/blue SiNPs, due to the convenient surface modification and biocompatibility of Au@Pt nanoparticles, which were used as labels for ICA. The detection was performed on an ICA strip by using the sandwich immunoreaction between HBsAg and the anti-HBsAg antibody and the accumulation of Au@Pt/blue SiNPs in the test zone. The results were qualitatively analyzed by the naked eye and quantitatively analyzed by the combination of a camera and "ImageJ" software, eliminating any lab equipment. The sensitivity of the Au@Pt/blue SiNP based ICA was lowered 20 times and 10 times compared with blue silica nanoparticles (blue SiNPs) and gold nanoparticles (AuNPs) as the reporter probe, respectively. Under optimal conditions, a linear relationship between the color intensity and HBsAg over the range of 0.5–10 ng mL −1 was achieved, and the detection limit was estimated to be 0.13 ng mL −1 (S/N = 3). The Au@Pt/blue SiNP based ICA, thus, offered a sensitive method for rapidly detecting HBsAg. Although the proof-of-concept of the Au@Pt/blue SiNP based ICA was demonstrated using HBsAg as a model analyte, this nanocomposite label based ICA can be easily developed to be a universal signal amplification technique and applied to the detection of other protein biomarkers.